Tecnonecromancia y Cyborg n° 3 - Villafuerte Villafuerte, Adriana (2024)
The objective of this project was to continue working and delving into the idea of death and mourning that I developed in 2021, this time in a new phase: that of post-mourning. In that sense, I attempt to make visible the ghost of mourning through the aesthetic proposal of the technological reliquary, the Cyborg n°3 or necromantic cyborg, in order to promote reflective thinking about the fear of loss and the fear of losing the “object” itself. Among the materials that I have used so far for the small sculptures are sheets of thermofilm, glass silicone, PVC plastic tubing, fishing line, cold porcelain, coloured earth, copper wires and galvanized wires. For the two-dimensional pieces I used pastels, charcoal and bistro, on paper and on canvas. As methodologies, from the theoretical side I used office research, as well as interviews and conversations with professors, psychologists, doctors, coaches and thanatologists. I also spoke with people who had suffered a loss or death in their lives between 2020 and 2022. In addition, I made notes of my own behaviour and cognitive-affective processes throughout this period, which coincided with the death of my mother in the year 2021. From the plastic side, I collected artistic references, I experimented with materials and with the written text. Likewise, I intend to work with sound as well. This proposal is still in process in terms of execution, with less than half of the plastic work to be completed.